Летучий корабль: сказка / худож. К. Кашина - Кашина К. (Русские народные сказки, 2015)
Экземпляры: ф.5 (20160422) / Инвентарный номер: 52962 / Цена: 22.00. / Сис.шифр: Д / Авт.знак: Л 52 / ГРНТИ: 17.82.93 / ББК: 84